The Moderating Role of Intellectual Humility in the Adoption of ICT: A Study Across Life-Span - Bernabé-Valero, Gloria; Iborra-Marmolejo, Isabel; Beneyto-Arrojo, Maria J.; Senent-Capuz, Nuria (Frontiers in Psychology, 2018)
Literature has shown age-related differences in the adoption process. In this way, it is very important to encourage the adoption of ICT by the elderly, in order to maintain their independence in daily life. However, some specific cognitive variables were not considered in theoretical models until a decade ago. One of the emerging fields in this area is the science of learnable intelligence, which investigates the role of thinking dispositions. The variable which we have focused on is intellectual humility. For this propose, a sample of 306 participants from 18 to 87 years was selected. Age was selected as a predictor variable. Intellectual humility was tested as a moderator between ageing and ICT adoption, more precisely computer and mobile devices. The model fitted the theoretical proposal. However, the subscale known as Independence of the intellect and ego was the only one to fulfill all the requirements for the moderational analysis. The findings suggest a moderational effect that might enhance the ICT adoption. These results are of interest in the field of personal development and training purposes in life-span.